2020
DOI: 10.3390/ani10101841
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hepatitis E Virus in the Feces of Red Foxes (Vulpes vulpes)

Abstract: Orthohepeviruses (HEV) can infect a wide range of animals, showing a relatively strict host specificity; however, its zoonotic potential, natural transmission in the wildlife are less known. Several new HEV-like viruses have been identified in various animal species, including carnivores; however, the phylogenetic relationship among these viruses is poorly resolved, since some of them were known as rodent-related so far. The red fox, the most widespread carnivore worldwide, is a known reservoir of several viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although this trend is typical among pets (dogs and cats), the same cannot be said for wildlife, as evidenced by multiple identifications of viral RNA in different matrices. To date, HEV has been identified in the feces of wolves, red foxes, and lynxes and in the cavity transudates of red foxes [ 7 , [27] , [28] , [29] ]. Furthermore, in wild animals, exposure to the virus appears significantly higher, probably due to greater contact with reservoir hosts and therefore a greater possibility of contracting the infection through their ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Although this trend is typical among pets (dogs and cats), the same cannot be said for wildlife, as evidenced by multiple identifications of viral RNA in different matrices. To date, HEV has been identified in the feces of wolves, red foxes, and lynxes and in the cavity transudates of red foxes [ 7 , [27] , [28] , [29] ]. Furthermore, in wild animals, exposure to the virus appears significantly higher, probably due to greater contact with reservoir hosts and therefore a greater possibility of contracting the infection through their ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides wild boars, recognized as the wildlife reservoir of zoonotic HEV [ 6 ], natural orthohepevirus infections have been occasionally reported in a variety of wild animals, including carnivores such as mongooses, bears, leopard, ferrets, minks, and foxes [ 8 , 9 , 10 , 11 , 12 , 13 ]. We undertook this study to better understand the ecology of orthohepeviruses in Italian wolves and red foxes implementing the HEV diagnostic algorithm with a pan-orthohepeviruses molecular strategy [ 19 ] that has also been previously used to detect HEV-C2 in red foxes [ 16 ]. In our analysis, orthohepevirus RNA was identified in a wolf faecal sample (81236/Wolf/2019/ITA), and, unexpectedly, we observed that it displayed the highest genetic relatedness to HEV strains classified as Gt3 within the species Orthohepevirus A .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the species Orthohepevirus A , hepeviruses closely related to rat orthohepeviruses C (HEV-C1) [ 14 ], but clustering into a distinct genotype (HEV-C2), were detected in 2012 by metagenomic investigation in faecal samples from household pet ferrets in the Netherlands [ 11 ]. Since then, carnivore-derived HEV-C2 strains have been detected in liver and faecal specimens from farmed American minks in Denmark [ 13 ] and in faeces of red foxes in the Netherlands, Germany, and Hungary [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Red foxes (Vulpes vulpes) are the most common and widespread wild carnivores in Europe, and they are well-recognised hosts for many pathogens shared between wild and domestic animals and humans as well. Many of these pathogenic agents cause severe illnesses in domestic animals and may represent a significant threat to public health [1][2][3].…”
Section: Introductionmentioning
confidence: 99%